Dimethyl Sulfide Production from Dimethylsulfoniopropionate in Coastal Seawater Samples and Bacterial Cultures - Kiene, Ronald P. (1990)
Dimethyl sulfide (DMS) was produced immediately after the addition of 0.1 to 2 μM β-dimethylsulfonio-propionate (DMSP) to coastal seawater samples. Azide had little effect on the initial rate of DMS production from 0.5 μM added DMSP, but decreased the rate of production after 6 h. Filtration of water samples through membrane filters (pore size, 0.2 μm) greatly reduced DMS production for approximately 10 h, after which time DMS production resumed at a high rate. Autoclaving completely eliminated the production of DMS. The antibiotics chloramphenicol, tetracycline, kanamycin, and vancomycin all had little effect on the accumulation of DMS over the first few hours of incubation, but produced significant inhibition thereafter. The effects of individual antibiotics were additive. Chloroform over a range of concentrations (0.25 to 1.25 mM) had no effects on DMS production. Similarly, organic amendments, including acrylate, glucose, protein, and starch, did not affect DMS accumulation from DMSP. Acrylate, a product of the enzymatic cleavage of DMSP, was metabolized in seawater samples, and two strains of bacteria were isolated with this compound as the growth substrate. These bacteria produced DMS from DMSP. The sensitivity to inhibitors with respect to growth and DMSP-lyase activity varied from strain to strain. These results illustrate the significant potential for microbial conversion of dissolved DMSP to DMS in coastal seawater.